Liver volume is lower and associates with resting and dynamic blood pressure variability in chronic fatigue syndrome. Issue 3 (3rd July 2018) - Zalewski, Pawel; Finkelmeyer, Andreas; Frith, James; Maclachlan, Laura; Blamire, Andrew; Newton, Julia L.
ABSTRACT: Background: Chronic fatigue syndrome (CFS) in many cases is characterised by abnormal autonomic function and lower blood pressure (BP). In animals the liver is a capacitance vessel for BP homeostasis. We developed a novel liver magnetic resonance (MR) imaging technique to compare liver volume in CFS to controls, and to explore its role in cardiovascular physiology. Methods: Liver MR (single breath-hold, enhanced T1-weighted, high-resolution isotropic volume excitation 3-Tesla Achieva, NL) determined liver volume. Red cell and plasma volume were also measured. A 10 min resting cardiac autonomic assessment using beat-to-beat measurement (Taskforce; CNSystems) was followed by assessment of hemodynamic response to standing to determine blood pressure drop and return to baseline. Results: Forty-four CFS patients (age = 45.5, 34f/10 m, Fukuda criteria) and 10 age, activity and sex matched controls (age = 49.4, 7f/3 m) participated. Adjusted for body size, CFS patients had significantly reduced liver volumes (775 (101) ml/m2 v 846 (96) ml/m2; p  = 0.02). At rest, liver volume was unrelated to symptom severity, heart rate, BP or heart rate variability. Both increased systolic and diastolic low frequency (LF) BP variability (predominantly sympathetic) were associated with lower liver volumes. On standing, liver volume was unrelated to BP drop but was associated with successful BP return-to-baseline. Red cell and plasma volume were associated positively with liver volume. Multivariate analysis confirmed return-to-baseline BP on standing which was independently associated with liver volume. Conclusion: Liver volumes were smaller in CFS compared to controls. The relationship between return-to-baseline BP after standing and liver volume suggests, as in animals, that the liver is involved in maintenance of BP. Abbreviations: ACI: Accelerated cardiac index; BPV: Blood pressure variability; BRS: Baroreflex sensitivity; CFS: chronic fatigue syndrome; Chr: Chromium; CI: cardiac index; FIS: Fatigue impact scale; HF: High frequency; HRV: Heart rate variability; LF: Low frequency; MR: magnetic resonance; NU: normalised units; SD: Standardised deviation; PSD: power spectral density; SI: Stroke index; TPRI: Total peripheral resistance index